Decadal Wintertime Temperature Changes in East Asia During 1958–2001 and the Contributions of Internal Variability and External Forcing. Issue 14 (13th July 2020) - Luo, M.; Feng, J.M.; Xu, Z.F.; Chen, L.; Wang, J.; Wang, Y.L.; Lin, S.; Zhong, L.H.
Abstract: The winter temperature in East Asia from 1958 to 2001 has shown an obvious warming trend superposed with a large amplitude of decadal oscillations. To separate the relative contributions of external forcing and internal variability to the decadal change in winter temperature, we propose a method which combines reanalysis data, global atmosphere‐ocean coupled model outputs, and regional climate model. The results show that the weakening of the East Asian winter monsoon accounts for warming trend in the south Mongolia, the southeastern coast of Asia, and the adjacent seas to a large extent. In contrast, radiative forcing causes the warming trend in middle and high latitudes. The increasing concentration of aerosols could have resulted in local cooling in some areas. The winter temperature shows a decadal oscillation of 0.6 °C at a time scale of 8–20 a, which is mainly due to the oscillation of the Siberian‐Mongolia High and volcanic activities. The amplitude of temperature oscillations caused by volcanic activities was one third of that induced by the Siberian‐Mongolia High. Key Points: The winter warming in East Asia during 1958–2001 was due to greenhouse gas emissions and the weakening of the East Asia winter monsoon Radiative‐forced warming had a uniform pattern, while the warming caused by weakening monsoon was located in the eastern coast of Eurasia Volcanic aerosols caused an interdecadal oscillation of 0.2 °C, which was one third of the strength caused by internal variability